SIFAT PEMESINAN LIMA JENIS KAYU ASAL RIAU - Achmad Supriadi; Abdurachman (Jurnal Penelitian Hasil Hutan, 2018)
Wood machining is one of important utilization properties, especially for lesser known wood species. This paper determines the machining properties and possible utilization of punak (Tetramerista glabra Miq.), meranti bunga (Shorea teysmanniana Dryer ex Brandis), mempisang (Alphonsea spp.), suntai (Palaquium burckii H.J.L.), and pasak linggo (Aglaia argentea Blume) originated from Riau Province. The tests were conducted based on the modified testing standard of ASTM D-1666-64. Twenty samples of each species were machining tested for the work of planing, shaping, boring, turning, and sanding. Visual observation was performed using loupe 10x magnification. Research revealed that planing, shaping, boring, turning and sanding properties were significantly influenced by wood species. Punak and pasak linggo had good and very good machining properties. Mempisang had a wide range machining properties from poor to very good, while meranti bunga had poor to good machining properties. Lastly, suntai had a moderate to good machining properties. Regression analysis showed that higher specific gravity resulted in better machining properties. Wood with good to very good categories could be suggested as raw materials for various products. Mempisang and meranti bunga should be carefully handled, particularly in boring and turning processes.